Pengembangan Bahan Ajar Warisan Budaya Berbantuan Wordwall Menggunakan Model Problem Based Learning di Kelas V Sekolah Dasar - Widiya, Widiya; Desyandri, Desyandri (Darul Yasin Al Sys, 2025)
The study aims to develop cultural heritage teaching materials assisted by wordwall using the Problem Based Learning model in grade V of elementary school. The study uses the Research and Development (R&D) method using the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The trial subjects were conducted at SDN 158507 Sarudik and for the research subjects were conducted at SDN 152977 Sarudik1 and SDN 154499 Sarudik 2. Validation data collection was carried out by means of a questionnaire given to the three validators, material experts, language experts and media experts, as well as a practicality questionnaire filled out by teachers and students at the end of the learning. The results of the study showed that cultural heritage teaching materials assisted by wordwall obtained a material validation result of 76.25% (valid). Language validation was 76.6% (valid) and for media experts 87.5% (very valid). Practicality test in the trial school obtained results of 93.13 (very practical) student responses and 100% teacher responses and the results of the practicality test in the two research schools obtained 90.9% (very practical) trial teacher responses reached results of 90.6% (very practical). The effectiveness test in the trial school achieved results of 89.1% (very effective) and both research schools achieved results of 90.9% with a very effective category. The conclusion of the study is that cultural heritage teaching materials assisted by wordwalls using the Problem Based Learning model are proven to be valid, practical, and effective in supporting the learning process in grade V of elementary school.